Mobiliário de ofícios: as bancas de ourives - Mota, Rosa Maria Dos Santos (2018)
The goldsmith benches we will discuss in this article were used through centuries and until mid-twentieth century and were a piece of furniture used in the goldsmith workshops, serving as a support for the multiple tasks necessary to produce gold or silver ornaments. The structure of the portuguese goldsmith’s benches is characterized by a formal simplicity, the use of local wood and other resources, showing, therefore, a very regional character, while presenting clean and archaic lines common to all workshops and regions. Their essence resided in the type of work for which they were created, the place for where they were built, but also in the link with the physical traits of the men who used them and the way they performed their craft.